Incontinentia pigmenti inherited from a father with a low level atypical IKBKG deletion mosaicism: a case report - Miki Kawai; Atsuya Sugimoto; Yasunori Ishihara; Takema Kato; Hiroki Kurahashi (BMC, 2022)
Abstract Background Incontinentia pigmenti (IP) is an X-liked dominant genodermatosis caused by mutations of the IKBKG/NEMO gene. IP is mostly lethal in males in utero, and only very rare male cases with a somatic mosaic mutation or a 47,XXY karyotype have been reported. Case presentation We here report a case of an IKBKG gene deletion in a female infant presenting with a few blisters and erythema in her upper arms at birth. MLPA analysis revealed a rare 94 kb deletion in this patient, encompassing the IKBKG gene and IKBKGP pseudogene. PCR analysis indicated the presence of Alu elements at both ends of the deletion, suggesting non-allelic homologous recombination as an underlying mechanism. Notably, a low-level mosaic deletion was identified in her father's peripheral blood leukocytes by PCR, suggesting a rare father-to-daughter transmission of IP. Conclusion In family studies for an apparently sporadic IP case, parental analysis that includes the father is recommended due to the possibility of male mosaicism.